MODEL EVALUASI PRAKTIKUM KIMIA DI LEMBAGA PENDIDIKAN TENAGA KEPENDIDIKAN - Susilanigsih, Endang (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2012)
Penelitian ini bertujuan untuk memperoleh model evaluasi program yang teruji, untuk mengevaluasi kualitas praktikum kimia. Pengembangan model evaluasi program terdiri atas empat variabel sebagai komponen model yaitu: (1) environmemt context yang dieksplanasi menjadi environment, laboratory work, technology and society; (2) evaluasi Input; (3) evaluasi process; dan (4) evaluasi result yang disesuaikan dengan praktikum kimia analisis dasar. Penetapan konstruk instrumen terdiri atas instrumen penilaian model dan instrumen penilaian kinerja mahasiswa dilakukan melalui pendapat: (1) pakar evaluasi; (2) pakar psikometri, dan (3) praktisi laboratorium. Subjek coba penelitian ini terdiri atas mahasiswa dan praktisi. Uji model evaluasi program dilakukan dengan uji: (1) utility; (2) feasibility; (3) proprietly; dan (4) accuracy. Uji kecocokan model untuk mengetahui reliability komponen program dan goodness of fit index menggunakan program Lisrel. Hasil pe-nelitian menunjukkan bahwa evaluasi program yang dikembangkan diberi nama model ECIPR sudah teruji memenuhi kriteria: (1) utility; (2) feasibili-ty; (3) proprietly; dan (4) accuracy reliability untuk komponen Environment context =0,8649, input=0,8429, process=0,7828, result=0,9560. Goodness of fit index: p = 0,107 RMSEA=0,051, GFI=0,910. Dampak implentasi model yang dikembangkan terbukti dapat meningkatkan kinerja mahasiswa, keterampilan dan pengalaman laboratorium mahasiswa sebagai sasaran program.Kata kunci: model evaluasi program, praktikum kimia, keterampilan laboratorium______________________________________________________________THE EVALUATION MODEL OF THE CHEMISTRY PRACTICUM IN TEACHER EDUCATION INSTITUTIONSAbstract This study aims to produce a program evaluation model which is valid to evaluate the quality of chemistry practicum. The program evaluation model consists of four variables as model components,i.e:(1) the context environment which is elaborated into environment, laboratory work, technology, and society; (2) the input evaluation; (3) the process evaluation; and (4) the result evaluation adjusted to basic analytic chemistry practicum.The establishment of the instrument constructs, consisting of a model evaluation instrument and a student performance evaluation instrument, was based on the opinions of (1) evaluation experts, (2) psychometrics experts, and (3) laboratory practitioners. The subjects for tryout in this research consisted of students and practitioners. The test of the program evaluation model was carried out on the basis of: (1) utility, (2) feasibility, (3) propriety, and (4) accuracy. The model fit test to find out the reliability of the program components and the goodness of fit index used the LISREL program package. The calculation of the reliability coefficient of the instrument for the laboratory performance evaluation used the SPSS program based on the Generalizability coefficient model developed by Thorndike. The components of the variance were the person, rater, item, interactions of the person and rater, the person and item, the rater and item, and the interaction of the person, rater and item.The results of the study show that the ECIPR program evaluation model is valid and satisfies the criteria for: (1) utility, (2) feasibility, (3) propriety, and (4) accuracy. The indicator reliability of the component of environment context is 0.8649, that of the input is 0.8429, that of the process is 0.7828, and that of the result is 0.9560. The goodness of fit index is indicated by p = 0.107, RMSEA = 0.051, and GFI = 0.910. The generalizability coefficient of the qualitative analytic instrument is 0.8726 and that of the quantitative analytic instrument is 0.9384. The implementation of the ECIPR model has been proved capable of improving the students' performances, which have effects on the improvement of their laboratory skills and experiences as the program target.Keywords: program evaluation model, chemistry practicum, laboratory skills